A Multifunctional Nanodrug Co-Delivering VEGF-siRNA and Dexamethasone for Synergistic Therapy in Ocular Neovascular Diseases - Ma X; Cui Y; Zhang M; Lyu Q; Zhao J (International Journal of Nanomedicine)
Xiaochen Ma,1 Yubo Cui,2 Min Zhang,1 Qinghua Lyu,2 Jun Zhao2 1The Second Clinical Medical College, Jinan University, Shenzhen, Guangdong, People’s Republic of China; 2Department of Ophthalmology, Shenzhen People’s Hospital (The Second Clinical Medical College, Jinan University; The First Affiliated Hospital, Southern University of Science and Technology), Shenzhen, Guangdong, People’s Republic of ChinaCorrespondence: Qinghua Lyu; Jun Zhao, Department of Ophthalmology, Shenzhen People’s Hospital (The Second Clinical Medical College, Jinan University; The First Affiliated Hospital, Southern University of Science and Technology), Shenzhen, 518020, People’s Republic of China, Email a0129473@u.nus.edu; doctorzhaojun@163.comIntroduction: Oxidant stress, abnormal angiogenesis, and inflammation are three key factors contributing to the development of ocular neovascular diseases (ONDs). This study aims to develop a multifunctional nanodrug, DEX@MPDA-Arg@Si (DMAS), which integrates mesoporous polydopamine, vascular endothelial growth factor (VEGF)-siRNA, and dexamethasone (DEX) to address these therapeutic targets.Methods: Physicochemical properties of DMAS were measured using transmission electron microscopy and a nanoparticle size analyzer. The encapsulation efficiency and drug loading capacity of DMAS were measured using a UV-visible spectrophotometer. The in vivo therapeutic efficacy and ocular safety of DMAS were evaluated using three established mouse models, including the alkali burn-induced corneal neovascularization (CoNV) model, the oxygen-induced retinopathy (OIR) model, and the laser-induced choroidal neovascularization (CNV) model.Results: The DMAS nanoparticles demonstrated a uniform bowl-like shape with an average size of 264.9 ± 2.5 nm and a zeta potential of − 28.2 ± 4.2 mV. They exhibited high drug-loading efficiency (36.04 ± 3.60% for DEX) and excellent biocompatibility. In vitro studies confirmed its potent antioxidant, anti-inflammatory, and anti-apoptotic properties. In vivo, DMAS treatment led to significant therapeutic effects across all models. It effectively inhibited CoNV, promoted corneal repair, and modulated inflammation in the alkali burn model. In the OIR model, DMAS reduced retinal neovascularization by decreasing VEGF expression. In the laser-induced CNV model, it significantly reduced the CNV area and lesion thickness.Conclusion: This research developed a multifunctional nanodrug, DMAS, capable of co-delivering VEGF-siRNA and DEX, offering synergistic therapeutic benefits for treating ONDs. The DMAS nanodrug demonstrates promising anti-inflammatory, antioxidative, and anti-angiogenic effects, highlighting its potential as a versatile and effective treatment for multiple ocular conditions.Keywords: mesoporous polydopamine, nano-delivery platform, ocular neovascular diseases, dexamethasone, VEGF-siRNA